Impact of the Post COVID-19 Condition in Peru. An Overview. - León-Figueroa , Darwin A. (2024)
Persistent COVID-19, also known as Post COVID-19 Condition (PCC) or post-acute sequelae of SARS-CoV-2 infection, affects approximately 10% to 20% of people who have had COVID-19. This condition is characterized by a variety of medium- and long-term symptoms after recovery from the initial illness, including fatigue, shortness of breath, muscle aches, cognitive problems, depression, and anxiety, among others. Diagnosis is based on the patient's symptoms and medical history, usually after 3 months from the onset of COVID-19. PCC affects more women and people with poor health conditions and is related to a history of asthma, obesity, and smoking. In Peru, around 300,000 people suffer prolonged symptoms that affect their daily and working lives, with limited access to medical care, especially in remote or low-income communities. It is essential to increase public awareness of PCC and its effects, promoting prevention through vaccination and ongoing care.